IMPLEMENTASI MEDIA PEMBELAJARAN SEJARAH BERBASIS E-KOMIK H-CLASS UNTUK SISWA KELAS X SMA DI JAWA TIMUR - Vinda Regita Cahyani; Moch Nurfahrul Lukmanul Khakim; Afiani Arofatul Zidah; Akbar Maulana Malik Ibrahim; Yohanes Purwanto (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The rapid development of technology affects all fields, including the field of education. Technological developments in the world of education are usually in the form of learning media that are used to support learning processes and objectives. Based on research data on learning history in several high schools in East Java, learning history is often considered boring, so innovations are needed that can attract students' interest in learning and are in accordance with existing technological developments, one of which is comic-based E-media learning. By using the